اعادة هندسة العمليات التشغيلية بهدف ترشيد كلف الوقود: بالتطبيق على افران في محافظة نينوى لإنتاج الصمون - هشام عمر الحديدي (PROSPECTIVE RESEARCHES, 2023)
Fuel costs are classified as indirect materials costs and that means the materials will not connect directly with product construction but considered as operating materials costs, and these costs increase quickly due to many reasons so they act on putting the price. The prices of most products that connected with these costs are raised many times , so the needing of reengineering operating process are used. The re-engineering operating process are considered as one of relatively modern methods that try to mix many jobs in one and try also to re-engineering production lines in way that achieve higher outputs with low inputs so the applying on products which affected by fuel prices raises. The reducing of fuel costs by using reengineering operating process approach in bakery which we made our research on , led us to achieve more flexibility in work hours , quality demand and more quantities of products .